Method for improving corrosion resistance of surface of micro pipe
By using alkaline liquid soaking, ultrasonic cleaning, dilute H3PO4 activation, silanization treatment and aqueous sealant sealing on nickel alloy micropipes, a cured film is formed, which solves the problem of poor corrosion resistance of nickel alloy micropipes and significantly improves its corrosion resistance and biocompatibility.
Patent Information
- Application Number
- CN202411638928.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-04
AI Technical Summary
Nickel alloy micropipes are prone to internal and external surface defects during casting, and the material has a large specific surface area, resulting in poor corrosion resistance and cannot meet the needs of 48-hour salt spray or biocompatibility, which limits its application in the fields of corrosion-resistant electronic testing probes and biomedical.
The solidified film is formed to improve the corrosion resistance of the pipe by using alkaline liquid soaking, ultrasonic cleaning, dilute H3PO4 activation, silanization treatment and aqueous sealant sealing.
It significantly improves the corrosion resistance of the surface of microtubes, can pass the salt spray test to produce corrosion-free pits, and shows good biocompatibility in the field of biomedical science.
Smart Images

Figure CN119553259A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nickel alloys, in particular to a method for improving the corrosion resistance of a micro-tube surface. Background Art
[0002] Electroformed nickel alloy microtubes (tubes with an outer diameter of 0.1-0.5mm and a length of no longer than 20mm) are prone to internal and external surface defects during the casting process. In addition, the material has a large specific surface area, so its corrosion resistance is poor and cannot meet the requirements of 48-hour salt spray or biocompatibility. This limits the application of the tubes in the field of corrosion-resistant electronic test probes and biomedical fields. Summary of the invention
[0003] In view of the shortcomings of the prior art, the present invention provides a method for improving the corrosion resistance of the surface of micro-tubes, which solves the problems raised in the above-mentioned background technology.
[0004] To solve the above technical problems, according to one aspect of the present invention, more specifically, a method for improving the corrosion resistance of the surface of micro-tubes comprises the following steps:
[0005] S1. Place the pipe in the cleaning tank and pour the alkaline liquid into the cleaning tank. Let it stand for 30 minutes at a temperature of 50°C. The alkaline liquid must cover the pipe.
[0006] S2. Place the ultrasonic device on the surface of the cleaning tank and clean the pipe 1-3 times with the ultrasonic device, with each cleaning time being 3-5 minutes;
[0007] S3, placing the pipe into the activation tank, pouring 1% H3PO4, and using ultrasonic equipment to ultrasonically activate the nickel-based pipe for 40 seconds;
[0008] S4, placing the activated pipe in a silanization tank and immersing it in ultrasound for 3 minutes using an ultrasonic device;
[0009] S5. First, heat the water phase sealant to 55°C, place the silanized pipe into the water phase sealant, and perform ultrasonic treatment for 1-2 minutes;
[0010] S6. Place the pipe in a vacuum thermostat to maintain 0.5 atmospheres of pressure. Set the temperature of the vacuum thermostat to 90°C and let it stand for 30 minutes.
[0011] Furthermore, in S2, during the ultrasonic cleaning, the power output by the ultrasonic equipment needs to be regulated according to the seismic performance of the pipe. The power output by the ultrasonic equipment is calculated as follows:
[0012]
[0013] In the formula, P is the power of ultrasound; c is the propagation speed of ultrasound in the pipe; m is the wavelength of ultrasound in the pipe; U is the potential difference between two points in a uniform electric field; d is the distance between the two points along the field intensity direction; ρ is the density of the pipe; A is the radiation area of ultrasound; G is the conductivity; L is the length of the medium; I is the cross-street area of the medium; V is the volume of the pipe;
[0014] The calculation formula for the vibration on the pipe surface is:
[0015]
[0016] Where HV is the vibration of the pipe; P is the power of the ultrasonic wave; and D is the pressure of the pipe.
[0017] Furthermore, in S5, the liquid in the silanization tank includes hexamethyldisilane, trimethylchlorosilane and pyridine, and the components of the silanization reagent are configured in a volume ratio of 3 ml of hexamethyldisilane, 1 ml of trimethylchlorosilane and 9 ml of pyridine according to mass.
[0018] Furthermore, in S3, S4 and S5, after the pipes are cleaned, activated and silanized, they are centrifuged 1-2 times in a centrifuge to prevent residual liquid on the surface of the pipes, and are washed with clean water after centrifugation and then centrifuged 1-2 times in a centrifuge.
[0019] Furthermore, the water phase sealant in the S5 has the following models: GT-2T, 1040C, GS0782, EC0680;
[0020] Take 200ml (10%) of GT-2T and preheat it at 50℃, then add it into the pipe to be treated and ultrasonicate it for 1-2min, and clean the pipe twice;
[0021] The concentration of 1040C is suitable to be 120ml / L. It should be preheated at 60℃, and then added to the pipe to be treated for 3-5 minutes of ultrasound. Finally, the pipe should be cleaned to make the water conductivity of the previous step reach below 5.
[0022] GS0782 is acidic, colorless and transparent. The optimum concentration is 150ml / L (1:6 with water). The optimum pre-treatment temperature is 50℃. The ultrasonic treatment time of the pipe is 3-5min, and finally it is washed with water twice.
[0023] The optimum concentration of EC0680 is 100ml / L (1:9 with water), the pre-treatment temperature is 55℃, the ultrasonic soaking time of the pipe is 3-5min, and finally it is washed twice with water;
[0024] After the salt spray test, the untreated pipe showed dense corrosion pits on the surface. After the salt spray test, the appearance of GT-2T changed from bright to matte, and no corrosion pits appeared; after the salt spray test, the appearance of 1040C changed from bright to light marks, and there were no corrosion pits; GS0782 and EC0680 had similar effects after the salt spray test, with the appearance changing from bright to small spots, and no corrosion pits. Compared with the untreated pipe, the impedance of the pipes treated with the four sealants was not significantly affected, and was in the range of 10-12mΩ.
[0025] Furthermore, in S6, the calculation formula for the corrosion resistance of the pipe after curing in the vacuum thermostat is:
[0026]
[0027] Where K is the corrosion resistance of the pipe; W0 is the mass of the pipe before corrosion; W1 is the mass of the pipe after corrosion; S is the surface area of the pipe; T is the corrosion time; V is the volume loss caused by corrosion; C is the surface area of the corrosion area; and F is the corrosion protection efficiency of the pipe.
[0028] The beneficial effects of the method for improving the corrosion resistance of the micro-tube surface of the present invention are:
[0029] The present invention soaks the pipe with alkaline liquid, and further cleans the pipe with ultrasonic equipment. After that, the pipe is placed in an activation tank, and the nickel-based pipe is activated by dilute H3PO4 and ultrasonic equipment. The activated pipe is placed in a silanization tank, and the pipe is silanized by ultrasonic equipment and a silanization agent. After a layer of silanization is performed on the surface, a water phase sealing agent is further used to seal the pipe. The pipe is placed in a vacuum thermostat and allowed to stand to solidify. After solidification, a solidified film is formed on the surface of the pipe, and the corrosion resistance of the pipe is improved by the solidified film. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The present invention is further described in detail below with reference to the accompanying drawings and specific implementation methods.
[0031] Figure 1 It is a structural schematic diagram of the present invention. DETAILED DESCRIPTION
[0032] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other without conflict.
[0033] like Figure 1 According to one aspect of the present invention, there is provided a method for improving the corrosion resistance of the surface of a micro-tube, comprising the following steps:
[0034] S1. Place the pipe in the cleaning tank and pour the alkaline liquid into the cleaning tank. Let it stand for 30 minutes at a temperature of 50°C. The alkaline liquid must cover the pipe.
[0035] S2. Place the ultrasonic device on the surface of the cleaning tank and clean the pipe 1-3 times with the ultrasonic device, with each cleaning time being 3-5 minutes;
[0036] S3, placing the pipe into the activation tank, pouring 1% H3PO4, and using ultrasonic equipment to ultrasonically activate the nickel-based pipe for 40 seconds;
[0037] S4, placing the activated pipe in a silanization tank and immersing it in ultrasound for 3 minutes using an ultrasonic device;
[0038] S5. First, heat the water phase sealant to 55°C, place the silanized pipe into the water phase sealant, and perform ultrasonic treatment for 1-2 minutes;
[0039] S6. Place the pipe in a vacuum thermostat to maintain 0.5 atmospheres of pressure. Set the temperature of the vacuum thermostat to 90°C and let it stand for 30 minutes.
[0040] In this embodiment, in S2, during the ultrasonic cleaning, the power output by the ultrasonic equipment needs to be regulated according to the seismic performance of the pipe. The power output by the ultrasonic equipment is calculated as follows:
[0041]
[0042] In the formula, P is the power of ultrasound; c is the propagation speed of ultrasound in the pipe; m is the wavelength of ultrasound in the pipe; U is the potential difference between two points in a uniform electric field; d is the distance between the two points along the field intensity direction; ρ is the density of the pipe; A is the radiation area of ultrasound; G is the conductivity; L is the length of the medium; I is the cross-street area of the medium; V is the volume of the pipe;
[0043] The calculation formula for the vibration on the pipe surface is:
[0044]
[0045] Where HV is the vibration of the pipe; P is the power of the ultrasonic wave; and D is the pressure of the pipe.
[0046] In this embodiment, in S5, the liquid in the silanization tank includes hexamethyldisilane, trimethylchlorosilane and pyridine, and the components of the silanization reagent are configured in a volume ratio of 3 ml of hexamethyldisilane, 1 ml of trimethylchlorosilane and 9 ml of pyridine according to mass.
[0047] In this embodiment, in S3, S4 and S5, after the pipes are cleaned, activated and silanized, they are centrifuged 1-2 times to prevent liquid from remaining on the surface of the pipes, and then washed with clean water and centrifuged 1-2 times again.
[0048] In this embodiment, the water phase sealing agent in S5 has the following models: GT-2T, 1040C, GS0782, EC0680;
[0049] Take 200ml (10%) of GT-2T and preheat it at 50℃, then add it into the pipe to be treated and ultrasonicate it for 1-2min, and clean the pipe twice;
[0050] The concentration of 1040C is suitable to be 120ml / L. It should be preheated at 60℃, and then added to the pipe to be treated for 3-5 minutes of ultrasound. Finally, the pipe should be cleaned to make the water conductivity of the previous step reach below 5.
[0051] GS0782 is acidic, colorless and transparent. The optimum concentration is 150ml / L (1:6 with water). The optimum pre-treatment temperature is 50℃. The ultrasonic treatment time of the pipe is 3-5min, and finally it is washed with water twice.
[0052] The optimum concentration of EC0680 is 100ml / L (1:9 with water), the pre-treatment temperature is 55℃, the ultrasonic soaking time of the pipe is 3-5min, and finally it is washed twice with water;
[0053] After the salt spray test, the untreated pipe showed dense corrosion pits on the surface. After the salt spray test, the appearance of GT-2T changed from bright to matte, and no corrosion pits appeared; after the salt spray test, the appearance of 1040C changed from bright to light marks, and there were no corrosion pits; GS0782 and EC0680 had similar effects after the salt spray test, with the appearance changing from bright to small spots, and no corrosion pits. Compared with the untreated pipe, the impedance of the pipes treated with the four sealants was not significantly affected, and was in the range of 10-12mΩ.
[0054] In this embodiment, in S6, the calculation formula for the corrosion resistance of the pipe after curing in the vacuum thermostat is:
[0055]
[0056] Where K is the corrosion resistance of the pipe; W0 is the mass of the pipe before corrosion; W1 is the mass of the pipe after corrosion; S is the surface area of the pipe; T is the corrosion time; V is the volume loss caused by corrosion; C is the surface area of the corrosion area; and F is the corrosion protection efficiency of the pipe.
[0057] Example 1
[0058] S1. Place the sandblasted pipe in a cleaning tank, and pour alkaline liquid into the cleaning tank and let it stand for 30 minutes at a temperature of 50°C. The alkaline liquid must cover the pipe.
[0059] S2. Place the ultrasonic device on the surface of the cleaning tank and clean the pipe 1-3 times with the ultrasonic device;
[0060] S3, placing the pipe into the activation tank, pouring H3PO4, and using ultrasonic equipment to ultrasonically activate the nickel-based pipe for 40 seconds;
[0061] S4, placing the activated pipe in a silanization tank and immersing it in ultrasound for 3 minutes using an ultrasonic device;
[0062] S5. First, heat the water phase sealant to 55°C, place the silanized pipe into the water phase sealant, and perform ultrasonic treatment for 1-2 minutes;
[0063] S6. Place the pipe in a vacuum thermostat to maintain 0.5 atmospheres of pressure. Set the temperature of the vacuum thermostat to 90°C and let it stand for 30 minutes.
[0064] Example 2
[0065] S1. Place the sandblasted pipe in a cleaning tank, and pour acidic liquid into the cleaning tank and let it stand for 30 minutes at a temperature of 50°C. The acidic liquid must cover the pipe.
[0066] S2. Place the ultrasonic device on the surface of the cleaning tank and clean the pipe 1-3 times with the ultrasonic device;
[0067] S3, placing the pipe into the activation tank, and using ultrasonic equipment to ultrasonically activate the nickel-based pipe for 1 minute;
[0068] S4, placing the activated pipe in a silanization tank and soaking it in ultrasound for 5 minutes using an ultrasonic device;
[0069] S5. First, heat the water phase sealant to 55°C, place the silanized pipe into the water phase sealant, and perform ultrasonic treatment for 1-2 minutes;
[0070] S6. Place the pipe in a vacuum thermostat and maintain it at 0.5 atmospheres. Set the temperature of the vacuum thermostat to 75°C and let it stand for 45 minutes.
[0071] Comparative Example 1
[0072] The iron-based waste containing Cr, Ni, V, Mn metal elements, Al2O3 and SiO2 is baked at 200°C to remove water vapor and impurities, sieved to obtain -80 mesh powder, and evenly mixed with reducing agent Al powder. The mass ratio of Al powder to iron-based waste is 1:10. The mixture is evenly loaded into a pipe making machine, and the centrifuge is started. When the speed reaches 800 rpm, the mixture is ignited by tungsten wire to cause SHS centrifugal reaction sintering. Under the action of centrifugal force, a "sandwich" structure pipe is formed, which is composed of a ceramic layer 1, an iron alloy layer 2 and a steel pipe matrix layer 3 from the inside to the outside, and an anti-corrosion layer is coated on the surface of the pipe.
[0073] Comparative Example 2
[0074] The iron-based waste containing metal elements such as Cr, Ni, V, Mn, Al2O3 and SiO2 is baked at 300°C to remove water vapor and impurities, and is sieved to obtain -120 mesh powder, which is evenly mixed with reducing agent Al powder in a mass ratio of Al powder: iron-based waste of 1:5. The mixture is evenly loaded into a pipe making machine, and the centrifuge is started. When the speed reaches 1200 rpm, the mixture is ignited by tungsten wire to cause SHS centrifugal reaction sintering, and a "sandwich" structure steel pipe is formed under the action of centrifugal force. From the inside to the outside, there are ceramic layer 1, ferroalloy layer 2 and steel pipe matrix layer 3, and an anti-corrosion layer is coated on the surface of the pipe.
[0075] Comparative Example 3
[0076] The iron-based waste containing metal elements such as Cr, Ni, V, Mn, Al2O3 and SiO2 is baked at 400°C to remove water vapor and impurities, and is sieved to obtain -180 mesh powder, which is evenly mixed with reducing agent Al powder in a mass ratio of Al powder: iron-based waste of 1:1. The mixture is evenly loaded into a pipe making machine, and the centrifuge is started. When the speed reaches 1400 rpm, the mixture is ignited by tungsten wire to cause SHS centrifugal reaction sintering. Under the action of centrifugal force, a "sandwich" structured steel pipe is formed, which is composed of a ceramic layer 1, an iron alloy layer 2 and a steel pipe matrix layer 3 from the inside to the outside, and an anti-corrosion layer is coated on the surface of the pipe.
[0077] The anti-corrosion performance, pipe strength, pipe hardness and pipe impact resistance of the pipes prepared in the examples and comparative examples were tested. The specific data are shown in Table 1.
[0078]
[0079] Table 1
[0080] As shown in Table 1, the pipe obtained by activation, silanization agent immersion, and vacuum thermostat fixation in the present invention has higher corrosion resistance, pipe strength, pipe hardness, and pipe impact resistance than the pipes obtained in Comparative Examples 1, 2, and 3.
[0081] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention also fall within the protection scope of the present invention.
Claims
1. A method for improving the corrosion resistance of a micro-tube surface, comprising the following steps: S1. Place the pipe in the cleaning tank and pour the alkaline liquid into the cleaning tank. Let it stand for 30 minutes at a temperature of 50°C. The alkaline liquid must cover the pipe. S2. Place the ultrasonic device on the surface of the cleaning tank and clean the pipe 1-3 times with the ultrasonic device, with each cleaning time being 3-5 minutes; S3, placing the pipe into the activation tank, pouring 1% H3PO4, and using ultrasonic equipment to ultrasonically activate the nickel-based pipe for 40 seconds; S4, placing the activated pipe in a silanization tank and immersing it in ultrasound for 3 minutes using an ultrasonic device; S5. First, heat the water phase sealant to 55°C, place the silanized pipe into the water phase sealant, and perform ultrasonic treatment for 1-2 minutes; S6. Place the pipe in a vacuum thermostat to maintain 0.5 atmospheres of pressure. Set the temperature of the vacuum thermostat to 90°C and let it stand for 30 minutes.
2. A method for improving the corrosion resistance of micro-tube surface according to claim 1, characterized in that: In S2, during the ultrasonic cleaning, the power output by the ultrasonic equipment needs to be regulated according to the seismic performance of the pipe. The power output by the ultrasonic equipment is calculated as follows: In the formula, P is the power of ultrasound; c is the propagation speed of ultrasound in the pipe; m is the wavelength of ultrasound in the pipe; U is the potential difference between two points in a uniform electric field; d is the distance between the two points along the field intensity direction; ρ is the density of the pipe; A is the radiation area of ultrasound; G is the conductivity; L is the length of the medium; I is the cross-street area of the medium; V is the volume of the pipe; The calculation formula for the vibration on the pipe surface is: Where HV is the vibration of the pipe; P is the power of the ultrasonic wave; and D is the pressure of the pipe.
3. A method for improving the corrosion resistance of micro-tube surface according to claim 1, characterized in that: In S5, the liquid in the silanization tank includes hexamethyldisilane, trimethylchlorosilane and pyridine, and the components of the silanization reagent are configured in a volume ratio of 3 ml of hexamethyldisilane, 1 ml of trimethylchlorosilane and 9 ml of pyridine according to mass.
4. The method for improving the corrosion resistance of the micro-tube surface according to claim 1, characterized in that: In S3, S4 and S5, after the pipes are cleaned, activated and silanized, they are centrifuged 1-2 times to prevent liquid from remaining on the surface of the pipes. After centrifugation, they are washed with clean water and centrifuged 1-2 times again.
5. The method for improving the corrosion resistance of the micro-tube surface according to claim 1, characterized in that: The water phase sealant in S5 has the following models: GT-2T, 1040C, GS0782, EC0680; Take 200ml (10%) of GT-2T and preheat it at 50℃, then add it into the pipe to be treated and ultrasonicate it for 1-2min, and clean the pipe twice; The concentration of 1040C is suitable to be 120ml / L. It should be preheated at 60℃, and then added to the pipe to be treated for 3-5 minutes. Finally, the pipe should be cleaned to make the water conductivity of the previous step reach below 5. GS0782 is acidic, colorless and transparent. The optimum concentration is 150ml / L (1:6 with water). The optimum pre-treatment temperature is 50℃. The ultrasonic treatment time of the pipe is 3-5min, and finally it is washed with water twice. The optimum concentration of EC0680 is 100ml / L (1:9 with water), the pre-treatment temperature is 55℃, the ultrasonic soaking time of the pipe is 3-5min, and finally it is washed twice with water; After the salt spray test, the untreated pipe showed dense corrosion pits on the surface. After the salt spray test, the appearance of GT-2T changed from bright to matte, and no corrosion pits appeared; after the salt spray test, the appearance of 1040C changed from bright to light marks, and there were no corrosion pits; GS0782 and EC0680 had similar effects after the salt spray test, with the appearance changing from bright to small spots, and no corrosion pits. Compared with the untreated pipe, the impedance of the pipes treated with the four sealants was not significantly affected, and was in the range of 10-12mΩ.
6. The method for improving the corrosion resistance of the micro-tube surface according to claim 1, characterized in that: In S6, the calculation formula for the corrosion resistance of the pipe after curing in a vacuum thermostat is: Where K is the corrosion resistance of the pipe; W0 is the mass of the pipe before corrosion; W1 is the mass of the pipe after corrosion; S is the surface area of the pipe; T is the corrosion time; V is the volume loss caused by corrosion; C is the surface area of the corrosion area; and F is the corrosion protection efficiency of the pipe.